2010
DOI: 10.1007/s00421-010-1663-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control influences lung membrane diffusion and oxygen saturation in exercise-trained subjects with type 1 diabetes

Abstract: Lung diffusing capacity (DLCO) is influenced by alveolar-capillary membrane conductance (D (M)) and pulmonary capillary blood volume (V (C)), both of which can be impaired in sedentary type 1 diabetes mellitus (T1DM) subjects due to hyperglycemia. We sought to determine if T1DM, and glycemic control, affected DLNO, DLCO, D (M), V (C) and SaO(2) during maximal exercise in aerobically fit T1DM subjects. We recruited 12 T1DM subjects and 18 non-diabetic subjects measuring DLNO, DLCO, D (M), and V (C) along with S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 65 publications
3
41
2
2
Order By: Relevance
“…In the 15 years prospective Coronary Artery Risk Development in Young Adults (CARDIA) study, ANS dysfunction in combination with poor physical fitness during young adulthood, was associated with a 3.4-fold increased risk of incident diabetes in middle-age [83]. A 15-month period of physical exercise in newly diagnosed T2DM patients significantly improved ANS function and glycemic control [81]. Twelve months of endurance and muscle strength training significantly improved exercise capacity, muscle strength, and BRS in patients with T2DM [82].…”
Section: The Beneficial Impact Of Exercise In Diabetesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the 15 years prospective Coronary Artery Risk Development in Young Adults (CARDIA) study, ANS dysfunction in combination with poor physical fitness during young adulthood, was associated with a 3.4-fold increased risk of incident diabetes in middle-age [83]. A 15-month period of physical exercise in newly diagnosed T2DM patients significantly improved ANS function and glycemic control [81]. Twelve months of endurance and muscle strength training significantly improved exercise capacity, muscle strength, and BRS in patients with T2DM [82].…”
Section: The Beneficial Impact Of Exercise In Diabetesmentioning
confidence: 93%
“…Although, impaired cardiac function, altered systemic oxygen tissue transport, arteriovenous oxygen difference and skeletal muscle metabolism have been associated with altered exercise responses in diabetes [81], the principal underlying pathophysiological process responsible for these limitations remains unknown and probably involves complex interplay between these pathways. Specific parameters related to myocardial function, i.e.…”
Section: Physiology and Exercise Capacity In Diabetesmentioning
confidence: 98%
“…Measurements of DLCO and DLNO were performed simultaneously with the measurement for Q which allowed for the assessment of D M and V C at rest and during each stage of exercise as previously described [23,25,35,55]. Briefly, Q, DLCO and DLNO were assessed using the rebreathe technique where subjects breathed through a pneumotachograph connected to a non-rebreathing Y-valve (Hans Rudolph, KC, MO) with the inspiratory port connected to a pneumatic switching valve.…”
Section: Protocolmentioning
confidence: 99%
“…Any alteration in pulmonary vasculature may lead to redistribution of pulmonary circulation, potentially causing ventilation/perfusion mismatch and impaired gas exchange. Recently, Wheatley et al have demonstrated that in diabetics the lung fails to recruit pulmonary capillaries in response to increased requests, as during physical exercise or after postural changes [57]. The same authors measured both DLCO and the transfer of nitric oxide (DLNO) in these patients, to distinguish between the two effects, namely the reduced pulmonary capillary blood volume and the reduction of alveolar-capillary membrane conductance.…”
Section: Pulmonary Diffusing Capacity For Carbon Monoxide (Dlco)mentioning
confidence: 99%